Emergent microsurgical intervention for acute stroke after mechanical thrombectomy failure: a prospective study - Fiedler, Jiří; Roubec, Martin; Grubhoffer, Marek; Ostrý, Svatopluk; Procházka, Václav; Langová, Kateřina; Školoudík, David; EMIAS Study Group (Journal of neurointerventional surgery, 2023)
BACKGROUND: Despite all the gains that have been achieved with endovascular mechanical thrombectomy revascularization and intravenous thrombolysis logistics since 2015, there is still a subgroup of patients with salvageable brain tissue for whom persistent emergent large vessel occlusion portends a catastrophic outcome. OBJECTIVE: To test the safety and efficacy of emergent microsurgical intervention in patients with acute ischemic stroke and symptomatic middle cerebral artery occlusion after failure of mechanical thrombectomy. METHODS: A prospective two-center cohort study was conducted. Patients with acute ischemic stroke and middle cerebral artery occlusion for whom recanalization failed at center 1 were randomly allocated to the microsurgical intervention group (MSIG) or control group 1 (CG1). All similar patients at center 2 were included in the control group 2 (CG2) with no surgical intervention. Microsurgical embolectomy and/or extracranial-intracranial bypass was performed in all MSIG patients at center 1. RESULTS: A total of 47 patients were enrolled in the study: 22 at center 1 (12 allocated to the MSIG and 10 to the CG1) and 25 patients at center 2 (CG2). MSIG group patients showed a better clinical outcome on day 90 after the stroke, where a modified Rankin Scale score of 0-2 was reached in 7 (58.3%) of 12 patients compared with 1/10 (10.0%) patients in the CG1 and 3/12 (12.0%) in the CG2. CONCLUSIONS: This study demonstrated the potential for existing microsurgical techniques to provide good outcomes in 58% of microsurgically treated patients as a third-tier option.
Keywords: ischemie mozku; endovaskulární výkony; Brain Ischemia; Humans; Stroke; kohortové studie; výsledek terapie; lidé; Cohort Studies; Ischemic Stroke; Thrombectomy; cévní mozková příhoda; trombektomie; Thrombolysis; Carotid Artery, Internal; Retrospective Studies; infarkt arteria cerebri media; arteria carotis interna; Treatment Outcome; Infarction, Middle Cerebral Artery; ischemická cévní mozková příhoda; retrospektivní studie; Endovascular Procedures; prospektivní studie; Prospective Studies